2022
DOI: 10.1093/cid/ciac171
|View full text |Cite
|
Sign up to set email alerts
|

Probable Animal-to-Human Transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Delta Variant AY.127 Causing a Pet Shop-Related Coronavirus Disease 2019 (COVID-19) Outbreak in Hong Kong

Abstract: Background SARS-CoV-2 can infect human and other mammals, including hamsters. Syrian (Mesocricetus auratus) and dwarf (Phodopus sp.) hamsters are susceptible to SARS-CoV-2 infection in the laboratory setting. However, pet shop-related COVID-19 outbreaks have not been reported. Methods We conducted an investigation of a pet shop-related COVID-19 outbreak due to Delta variant AY.127 involving at least three patients in Hong Kon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…There was limited local transmission in January 2022 due to several Omicron variant-related clusters which could be traced to imported cases (n=836), including a BA.1 outbreak in a restaurant and a large Omicron BA.2 outbreak in a housing estate which we reported previously 40,41 (Figure 4A). There was also a cluster of pet-storerelated Delta variant AY.127 42 . Since early February, 2022, there was an exponential increase in cases from <200 cases per day before February 4 to a peak of 76,991 cases (56,827 con rmed by nucleic acid test and 20,164 con rmed by self-collected rapid antigen test on March 3, 2022 43,44 .…”
Section: The Fth Wave Of Covid-19 In Hong Kongmentioning
confidence: 99%
See 2 more Smart Citations
“…There was limited local transmission in January 2022 due to several Omicron variant-related clusters which could be traced to imported cases (n=836), including a BA.1 outbreak in a restaurant and a large Omicron BA.2 outbreak in a housing estate which we reported previously 40,41 (Figure 4A). There was also a cluster of pet-storerelated Delta variant AY.127 42 . Since early February, 2022, there was an exponential increase in cases from <200 cases per day before February 4 to a peak of 76,991 cases (56,827 con rmed by nucleic acid test and 20,164 con rmed by self-collected rapid antigen test on March 3, 2022 43,44 .…”
Section: The Fth Wave Of Covid-19 In Hong Kongmentioning
confidence: 99%
“…We have previously reported our viral genome sequencing results for specimens collected up to February 2, 2022, including those from an Omicron BA.1 restaurant outbreak 41 , an Omicron BA.2 housing estate outbreak 40 , and a Delta AY.127 outbreak related to pet stores 42 . Here, we have performed additional sequencing for specimens collected in Hong Kong up to March 11, 2022 (Supplementary Table S2).…”
Section: Genomic Epidemiology Of the Fth Wave From January To March 2022mentioning
confidence: 99%
See 1 more Smart Citation
“…There was no local transmission in the next 40 days until two crew members of Cathay Pacific Airlines brought the virus to our communities. Although we successfully contained the transmission of the Omicron variant from these two sources and that of the Delta variant from hamsters in the pet stores to humans [ 2 ], the highly transmissible BA.2 subvariant of Omicron outcompeted our containment efforts. The explosive spreading of BA.2 was retrospectively determined to initiate from an incident in a quarantine hotel, where a South Asian woman was infected by other foreign quarantinees staying in another room and with no face-to-face contact.…”
mentioning
confidence: 99%
“…50 The origin of this case was associated with the SARS‐CoV‐2 δ variant AY.127 in Hong Kong, and an epidemiological investigation of these patients revealed that they were all associated with a local pet store. 7 , 8 , 51 SARS‐CoV‐2‐positive samples were found in environmental and hamster samples from pet stores as well as in the associated supply warehouses. However, the hamsters were not exhibiting clinical signs.…”
Section: Natural Infections In Animalsmentioning
confidence: 99%